1989
DOI: 10.1128/jvi.63.8.3535-3540.1989
|View full text |Cite
|
Sign up to set email alerts
|

Defect of adenovirus type 12 replication in hamster cells: absence of transcription of viral virus-associated and L1 RNAs

Abstract: The nonpermissive interaction of hamster cells with human adenovirus type 12 (Adl2) is characterized by a total block of Adl2 DNA replication and late transcription, whereas most of the early functions of Adl2 DNA can be transcribed. Ad2 can replicate in hamster cells. The replication and late transcription defects of Adl2 DNA can be complemented to a certain extent by the E1B functions of Ad2 DNA. This complementation fails, however, to lead to the synthesis of the late Adl2 proteins and to the assembly of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Among rodents, hamsters, and cotton rats have been proposed as suitable models for respiratory infection by human adenovirus (22,30,46). Hamster cells are permissive for Ad2 and Ad5 replication (35) but are significantly less permissive than human cells, while mouse cells are semipermissive (7,51). In this study, we found that porcine cell lines support Ad5 replication, showing virus kinetics and virus titers similar to those obtained for human epithelial cells.…”
Section: Discussionsupporting
confidence: 66%
“…Among rodents, hamsters, and cotton rats have been proposed as suitable models for respiratory infection by human adenovirus (22,30,46). Hamster cells are permissive for Ad2 and Ad5 replication (35) but are significantly less permissive than human cells, while mouse cells are semipermissive (7,51). In this study, we found that porcine cell lines support Ad5 replication, showing virus kinetics and virus titers similar to those obtained for human epithelial cells.…”
Section: Discussionsupporting
confidence: 66%
“…It seemed likely that there were several defects in the Adl2 genome to account for the abortive cycle of Adl2 in hamster cells. In previously published analyses, these defects had been localized to the E1B region (Klimkait and Doerfler, 1987), to the VA RNA region (Juttermann et al, 1989), and to the MLP of Adl2 DNA (Weyer and Doerfler, 1985). It was conceivable that these functions were somehow interdependent since all were subject to ElA regulation.…”
Section: Resultsmentioning
confidence: 99%
“…The levels of Adl2 ElA and E1B gene products in BHK21 cell extracts have been reported to be about 10% of those in human KB cell extracts (33). Late Adl2 genes or the virus-associated RNA region encoding virus-associated RNA are not transcribed in hamster cells (23). The block of Adl2 DNA replication and late-gene transcription in hamster * Corresponding author.…”
mentioning
confidence: 99%